Effects of power and radio frequency electromagnetic fields on human performance : a dissertation submitted in partial fulfillment for the degree of Doctor of Philosophy in Physiology, Massey University - Mobberley, Glenis Anne (Massey University, 2005)
Humans have been exposed to manmade electromagnetic fields (EMFs) since electricity was first harnessed in the 1800s. This exposure has accelerated in the last few decades with the widespread use of electrical appliances producing 50/60 Hz power frequency EMFs. With the advent of cellular phones (900 or 1800 MHZ) exposure frequencies have increased and wavelengths shortened. With this exposure has come a public concern over possible health effects from increasing exposure to EMFs, particularly in the radio frequency bands. Experiment One exposed 29 subjects to an EMF of 50 Hz, 100µT, pulsed (one second on/ one second off). Each subject attended at 12 p.m. and 12 a.m. on two consecutive days, a total of two control and two exposure sessions. Effects on salivary melatonin levels, and the cognitive parameters of working memory and attention were studied. Experiment Two exposed 50 subjects to almost the same protocol and experimental conditions. An additional control sample of saliva was obtained before each of the four sessions. There was no significant effect on attention or auditory working memory in either experiment. In Experiment One the presence of the EMF had no effect on salivary melatonin levels, including the subgroup of those with naturally low levels. In Experiment Two, a significant drop in melatonin levels was found for the day session, but only when compared to the same day control. This raised questions as to the reliability of using a separate day as a control due to excessive within-subject variation over the two days. There were no significant differences between male and female subjects in response to the EMF. Experiment Three investigated possible effects from a commercially available digital 900 MHz band cellular phone on melatonin levels, aural temperature, blood pressure, heart rate and the cognitive parameters of attention and memory. Forty-three subjects attended a single evening session. Two exposure sessions were surrounded by three control sessions. This was done to compensate for the natural change that occurs in melatonin levels, temperature and cardiac readings during an evening. Results were averaged for control sessions then compared to the average for the exposure sessions. A statistically significant rise in aural temperature was noted in both ears when the phone was operating. The difference was significantly greater on the side the phone was held. Scores in an attention test were also significantly lower when the phone was in use. The reduced attention level has implications for the safety of using of cellular phones whilst driving. Heating of the head may have biological consequences depending on the depth of penetration. There was no perceived effect on melatonin levels, no gender effects or effects on those with naturally low melatonin levels. Neither cardiac readings or numerical working memory were effected by exposure to a cellular phone.
Keywords: Electromagnetism; Physiological effects; Attention